2019
DOI: 10.1186/s12887-019-1669-2
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in gross motor function and muscle tone in children with cerebral palsy related to neonatal icterus: an open-label, uncontrolled clinical trial

Abstract: Background Although stem cell transplantation has been successfully performed for cerebral palsy (CP) related to oxygen deprivation, clinical trials involving the use of stem cell transplantation for CP related to neonatal icterus have not been reported. The aim of this study was to evaluate the effectiveness of transplantation of autologous bone marrow mononuclear cell (BMMC) for improving gross motor function and muscle tone in children with CP related to neonatal icterus. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Aging, injury, and acquired diseases can significantly change BMMNC components [ 28 ]. Some of our clinical trials using autologous BMMNCs for CP have shown the safety and initial effectiveness of the therapy [ 7 , 10 , 27 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging, injury, and acquired diseases can significantly change BMMNC components [ 28 ]. Some of our clinical trials using autologous BMMNCs for CP have shown the safety and initial effectiveness of the therapy [ 7 , 10 , 27 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, stem cell therapy for different neurologic conditions has become a new hope for patients. Bone marrow mononuclear cell therapy was one of the initial cell types used in clinical trials for the treatment of cerebral palsy [4,6,10,[24][25][26][27] and TBI [8,20]. Aging, injury, and acquired diseases can significantly change BMMNC components [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies report pulmonary embolisms and accumulation of transplanted cells in undesired peripheral organs ( Steiner et al, 2012 ; Jung et al, 2013 ; Wu Z. et al, 2017 ). Other more direct routes of transplantation are intrathecal (IT) and intra-cerebral (IC) ( Zali et al, 2015 ; Nguyen et al, 2017 ; Thanh et al, 2019 ). The complexity of brain structure and variable localizations of WMI likely influence the selection of proper transplantation route ( Henriques et al, 2019 ).…”
Section: Enhancing Oligodendrocytes Myelination As Therapeutic Strategies Against White Matter Injurymentioning
confidence: 99%
“…The number of BMMNCs that we collected each time is described in Table 1, and all the collected cells were used for transplantation. Based on our previous studies showing that BMMNC transplantation led to markedly improved gross motor function in patients with neurological complications such as cerebral palsy (12,35) and neurological sequelae due to intracranial hemorrhage (36), the ability of patient to sit up was selected as satisfactory criteria to evaluate if the patient needs additional transplantation. If the patient could not show the improvement as indicated by their ability to sit up after BMMNC transplantation, additional transplantation will be implemented but not more than four times.…”
Section: Autologous Bmmnc Collection Isolation and Transplantationmentioning
confidence: 99%